KAHOOT: A Game Based Platform for Learning Reading - Arif, M. Ichwan; Syafii, Ahmad (English Education Department STKIP Al Hikmah Surabaya, 2018)
This paper reviews Kahoot as a game based learning platform  particularly in reading. It provides teachers an opportunity to create game or quizzes and take the scores simultaneously. Moreover, through Kahoot, the students can work hand in hand with their group and compete each other with another group. This situation will enhance their intention to learn and increase their achievement. This research revealed that using Kahoot could increase students reading comprehension.